Explaining and Evaluating Transnational Tortious Actions against Parent Companies: Lessons from Shell and Nigeria. Issue 2 (May 2022) - Riley, Christopher; Akanmidu, Oludara
Abstract : In recent years, some of the most interesting and challenging corporate litigation has involved transnational tortious claims against parent companies. Such transnational cases raise a number of important issues which are downplayed in the literature addressing parental liability in purely 'domestic' cases. This article seeks to explore three such issues. The first concerns how we should explain victims' motives for suing the parent in these cases. We argue that transnational actions, unlike 'domestic' cases against parents, are less often a means of circumventing the subsidiary's insolvency, and more often about the search for a better forum, inflicting reputational damage on a corporate group, and avoiding doctrinal problems which may afflict the subsidiary action. The second issue is the legitimacy of using parental actions for these reasons. The third issue concerns whose law should govern transnational actions against parents. To illustrate these issues, we use three recent examples of transnational actions against parent companies.